Coaxial Pipes Used as Ground Buried Heat Exchangers—A Review of Research in Recent Years - Geng Wang; Nai Rong; Xuefei Li; Ning Hu; Zhi Zhang; Yuan Zhang; Yuhan Wang (Buildings)
The efficient utilization of geothermal energy depends heavily on high-performance ground heat exchangers. Coaxial pipe is a high-efficiency heat exchanger composed of two nested tubes of different diameters. In this paper, the structure and thermal exchange characteristics of coaxial pipe geothermal exchangers are introduced, which are superior to single-U and double-U geothermal exchangers in respect of installation, heat transporting, and deep geothermal application. Thermal test research of coaxial pipe geothermal exchangers is investigated. Relevant studies in recent years on the factors affecting the thermal performance of coaxial pipe ground heat exchangers, including exchanger configurations, circulating fluids, subsurface conditions, flow patterns, and operational modes, are reviewed. In addition, research on the impact of coaxial pipe ground heat exchangers on the ground, as well as applications for coaxial pipe ground heat exchangers, is summarized. Recommendations are made for potential future research on coaxial pipe ground heat exchangers. It is believed that the results of these studies will help to raise awareness of coaxial pipe ground heat exchangers and to continue to promote their application.